The application of evidence-entropy weight gray incidence theory on the risk assessment of rockburst intensity in the Daxiangling tunnel - Zhang, Xue-Jun; Gu, Xin-Bao (Frontiers in Earth Science, 2023)
The risk assessment of rock burst intensity is significant for tunnel construction safety. First, the depth of rockburst(X1), the uniaxial compressive strength of rocks (X2), the brittleness coefficient of rocks (X3), the stress coefficients of rocks (X4), the elastic energy index (X5) are adopted as the evidence body, their essential certainty reliability is determined using the entropy-gray correlation theory.Secondly, the synthetic certainty reliability of other samples is calculated based on the evidence theory. Relatively to the traditional gray extension model, it can improve the predictive accuracy and determine the certainty reliability of different evidence bodies.The difference of importance between other evidence bodies can be reflected; and an interval scale can be taken into consideration in the evaluation process, so the proposed theory can reasonably predict the grade criterion which is interval form.Conclusions demonstrated that the suggested approach is entirely consistent with the actual investigation. The proposed model not only considers the unreliability or reliability of the problem but also solves some degrees of uncertainty and ambiguity of the datum; it enhances the predictive efficiency and provides a new way and thought for future risk assessment of rockburst intensity.